Jeżeli ktos by mi pomógł bym był bardzo wdzięczny c1) 2 x [3 1/4 -(-3,75)] x 3,5
c2) (-10) x (1 1/5 - 5,5) d) 3 x (-10)2 + (-3)3 e) (-7) x (-10{do kwadratu}) -(-7)
f) (-9) x (-8) - 5 x (-10{do kwadratu}) dzięki


Odpowiedź :

Odpowiedź:

c1) 2 x [3 1/4 -(-3,75)] x 3,5= 2(13/4+3,75)x3,5=2(13/4 + 15/4)x3,5=2x7x3,5=49

c2)  (-10) x (1 1/5 - 5,5)=(-10)x(6/5-11/2)=(-10)x(-43/10)=43

d) 3 x (-10)2 + (-3)3=3x10²-27=3x100-27=300-27=273

e) (-7) x (-10{do kwadratu}) -(-7)=7x100+7=700+7=707

f) (-9) x (-8) - 5 x (-10{do kwadratu})=72+5x100=72+500=572

Odpowiedź:

c1) 2 * [3 1/4 - (- 3,75)] * 3,5 = 2 * [3,25 + 3,75] * 3,5 = 2 * 7 * 3,5 = 14 * 3,5 = 49

c2) (- 10) * (1 1/5 - 5,5) = (- 10) * (1,2 - 5,5) = (- 10) * (- 4,3) = 43

d) 3 * (- 10)² + (- 3)³ = 3 * 100 + (- 27) = 300 -27 = 273

e) (- 7) * (- 10)² - (- 7) = (- 7) * 100 + 7 = - 700 + 7 = - 693

f) (- 9) * (- 8) - 5 * (- 10)² = 72 - 5 * 100 = 72 - 500 = - 428

Szczegółowe wyjaśnienie: